Reflections on ‘Magical Thinking’ and Medieval Medicine - Knight, Gwendolyne (Circumscribere International Journal for the History of Science, 2022)
Magic is a slippery concept that has been notoriously difficult to pin down both across and within disciplines. While anthropological approaches to the study of magic in the past have been instrumental to the transformation of the field, comparatively less attention has been paid to the discussion of ‘magical thinking’ within the fields of medicine and psychology. This essay discusses the concept of ‘magical thinking’, and considers its significance for scholars of medicine and magic in the European Middle Ages.